Stability and performance investigations of model predictive controlled active-front-end (AFE) rectifiers for energy storage systems - Akter, M.P.; Mekhilef, Saad; Tan, N.M.L.; Akagi, H. (2015)
This paper investigates the stability and performance of model predictive controlled active-front-end (AFE) rectifiers for energy storage systems, which has been increasingly applied in power distribution sectors and in renewable energy sources to ensure an uninten-uptable power supply. The model predictive control (MPC) algorithm utilizes the discrete behavior of power converters to determine appropriate switching states by defining a cost function. The stability of the MPC algorithm is analyzed with the discrete z-domain response and the nonlinear simulation model. The results confirms that the control method of the active-front-end (AFE) rectifier is stable, and that is operates with an infmite gain margin and a very fast dynamic response. Moreover, the performance of the MPC controlled APE rectifier is verified with a 3.0 kW experimental system. This shows that the MPC controlled AFE rectifier operates with a unity power factor, an acceptable THD (4.0 ) level for the input current and a very low DC voltage ripple. Finally, an efficiency comparison is performed between the IVEPC and the VOC-based PWM controllers for AFE rectifiers. This comparison demonstrates the effectiveness of the MPC controller. '